Apresentação PBCIB n. 2, v. 16, 2021 - Araújo, Vania Rodrigues Hermes de; Freire, Isa Maria; Freire, Gustavo Henrique de Araújo (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2021)
Apresentação PBCIB n. 2, v. 16, 2021